Transformative HR : how great companies use evidence-based change for sustainable advantage - Boudreau, John W. (Jossey-Bass, 2011)
"Proven HR strategies that can have a real impact on organizational success. This book demonstrates how some of the world's most admired and prominent organizations are redefining HR leadership by using evidence-based change to inform human capital decisions that optimize efficiency, effectiveness and strategic impact. The authors present the five foundational principles to the new HR decision science: Logic-driven analytics, segmentation, risk leverage, synergy and integration and optimization. Includes practical suggestions and approaches to help executives put the book's principles into action Contains insight based on the experiences of leading global organization such as PNC Bank, CME Group, Royal Bank of Scotland, Deutsche Telekom and Shanda Interactive Entertainment Features in-depth case studies of 6 international companies: Coca-Cola, Khazanah Nasional Berhad, IBM, Ameriprise Financial, Royal Bank of Canada and Royal Bank of Scotland This groundbreaking book reveals a new approach to deliver sustainable change and business results. It is enhanced with success stories from leading companies that engage leadership and involve employees in ways that make a lasting impact on their companies"--